French Influence in the African Sahel: Opportunities and Challenges: international and political journal - Ali, Assist lec. Jihad Abbas (The International and Political Journal, 2025)
France aims to maintain its influence in the African continent in general and the Sahel countries in particular, by supporting these countries with weapons to fight terrorists and supporting leaders loyal to it with international legitimacy, which makes it the destiny in these countries, and despite French efforts, it meets the expansion of the influence of other countries such as the United States of America, China and other countries, which puts France in a test in order to achieve its goal.